011 HbA1c and mortality in diabetic individuals with heart failure: an observational cohort study. (16th May 2012) - Elder, D H J; Donnelly, L; Wong, A; Szwejkowski, B R; Pauriah, M; Lim, T K; Pringle, S D; Choy, A; Pearson, E; Morris, A; George, J; Struthers, A; et al.
Abstract : Background: Controversy exists regarding the importance of glycaemic control in patients with type 2 diabetes mellitus (T2DM) and chronic heart failure (CHF) based on conflicting reports that had used a single baseline HbA1c. Objective: To examine the relationship between the mean of all HbA1c measures after CHF diagnosis and outcome in a large cohort of T2DM patients with incident CHF. Design: Retrospective, observational cohort study. Setting: Tayside, Scotland. Patients: T2DM patients with incident CHF between 1993 and 2010. Measurement: A weighted mean HbA1c was calculated using all available HbA1c measures following CHF diagnosis and patients were grouped into five categories of HbA1c (≤6%, >6–≤7%, >7–≤8%, >8–≤9% and >9%). We subsequently compared diet and drug treated populations. The relationship between mean HbA1c and all-cause deaths after CHF diagnosis was assessed. Results: 795 patients with T2DM met study criteria. Median follow-up of 3.8 years saw 491 (61.8%) deaths. Cox regression model, adjusted for all other significant predictors, with the middle HbA1c category (>7–≤8%) as the reference, showed a U shaped relationship between HbA1c and outcome. (<6% [HR 95% CI 1.78 (1.26 to 2.52)]; >6–≤7% [1.29 (1.01 to 1.66)] and >9% [1.38 (1.03 to 1.84)]. We found a similar relationship in the drug treated sub-group. However in the diet only group, low HbA1c was associated with the lowest risk of death (≤7% [0.17 (0.07 to 0.39)]). Conclusions: In patients with T2DM and CHF, our observational study shows that in drug treated patients there was a U shaped relationship between HbA1c and mortality with the lowest mortality risk in patients with modest glycaemic control (HbA1c, >7–≤9%). However in diet treated patients, lower HbA1c was associated with lower mortality risk.